Exploring Tilly’s Theory : Violent Conflicts and Tax Revenue in Sub-Saharan Africa - (:unkn) unknown (My University, 2021)
This article explores the relationship between violent conflicts and tax revenue in Sub-Saharan countries. In a first stage, I estimate the effects of conflicts for 42 countries using panel data analysis. I find that an outbreak of violent conflict leads to an average 1.5 percent loss of tax revenue per capita. The results show that due to the outbreak of violence, government cannot successfully raise revenue, and because the conflict also negatively affects key macroeconomic variables, the tax base shrink and the overall loss is higher. The results also point to an important role of some specificities of Sub-Saharan countries such as ethnic division and natural resource endowment. Drawing on these results, I conduct case study for Central African Republic, Cote d’Ivoire, Congo Republic, Guinea and Guinea Bissau in a second stage using synthetic control method. The results show that the 2002 conflict in Cote d’Ivoire and the 1998 conflict in Guinea-Bissau led to significant drop in tax revenue. The outbreak of conflict did not have significant effects on tax revenue for the remaining three countries.
Keywords: African Research